Inequality Measurement and Tax/Transfer Policy - Patricia Apps; Ray Rees (Institute of Labor Economics (IZA), 2020)
We provide a critique of the standard methodology which bases welfare comparisons between households on deflating household income and consumption by an equivalence scale. We argue that this leads to support for tax/transfer policies that significantly disadvantage low to middle income households and women as second earners. We base the critique both on a theoretical model of the family household and a detailed analysis of Australian income and employment data.
Keywords: D13; D31; H21; H24; H31; 330; inequality; equivalence scales; tax/transfer policy; families